2009
DOI: 10.1002/ijc.24453
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of stanniocalcin 2 gene expression in colorectal cancer

Abstract: Laser microdissection (LMD) and microarray were used to identify genes associated with colorectal cancer. Stanniocalcin 2 (STC2) expression and clinicopathological significance in 139 clinical colorectal cancer samples were specifically investigated using real‐time quantitative reverse transcription‐polymerase chain reaction. A number of genes upregulated in colorectal cancer cells compared to normal colorectal epithelial cells were identified including STC2. STC2 gene expression in cancer tissue was higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 37 publications
2
57
0
Order By: Relevance
“…STC2 has recently been described to inhibit epithelial-mesenchymal transition through the PKC/claudin-1-mediated signaling in human breast cancer cells [45]. Previous studies have shown deregulated expression of STC2 in a variety of cancers, with its expression correlating with poor prognosis [45][46][47][48][49][50][51]. Although such studies Fig.…”
Section: Discussionmentioning
confidence: 96%
“…STC2 has recently been described to inhibit epithelial-mesenchymal transition through the PKC/claudin-1-mediated signaling in human breast cancer cells [45]. Previous studies have shown deregulated expression of STC2 in a variety of cancers, with its expression correlating with poor prognosis [45][46][47][48][49][50][51]. Although such studies Fig.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to a role in the cellular stress response, STC2 expression has been correlated with the development or severity of several types of cancer, including breast, prostate, renal, colorectal, and ovarian carcinomas (4,5,22,36,51). In fact, several of these studies have proposed using STC2 expression as a prognostic marker (5,15,26,36).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Stc1 Ϫ/Ϫ , Stc2 Ϫ/Ϫ , and Stc1 Ϫ/Ϫ Stc2 Ϫ/Ϫ mice do not exhibit any changes in serum Ca 2ϩ or phosphate levels and do not have any deficits in growth or fertility (8,9). While STC2 does not appear to play a physiologic role in the endocrine regulation of Ca 2ϩ homeostasis, numerous studies have demonstrated a link between STC2 expression and a variety of different cancers, including breast, prostate, renal, colorectal, and ovarian carcinomas (4,5,22,36,51). Other recent work has suggested that STC2 promotes invasiveness and metastasis in cancer cells (26,29,53).…”
Section: Camentioning
confidence: 99%
“…It has been reported that STC2 expression was upregulated in various tumors, including breast cancer [16,17], prostate cancer [18], esophageal squamous cell carcinoma (ESC) [19], gastric cancer [20], colorectal cancer [21], renal cell carcinoma (RCC) [22] and neuroblastoma [23]. Clinical and pathological studies reveal that STC2 overexpression correlates to advanced tumor grade, tumor invasiveness, metastasis and poor prognosis in prostate cancer, ESC, gastric cancer, colorectal cancer and RCC [18].…”
Section: Introductionmentioning
confidence: 99%